2019
DOI: 10.3390/app9132709
|View full text |Cite
|
Sign up to set email alerts
|

Periocular Recognition in the Wild: Implementation of RGB-OCLBCP Dual-Stream CNN

Abstract: Periocular recognition remains challenging for deployments in the unconstrained environments. Therefore, this paper proposes an RGB-OCLBCP dual-stream convolutional neural network, which accepts an RGB ocular image and a colour-based texture descriptor, namely Orthogonal Combination-Local Binary Coded Pattern (OCLBCP) for periocular recognition in the wild. The proposed network aggregates the RGB image and the OCLBCP descriptor by using two distinct late-fusion layers. We demonstrate that the proposed network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It was shown that in all cases an improvement between 3 and 5 percent was achieved when using both eyes instead of only one. Thus, most of the state-of-the art methods use the bi-ocular information, some of them analyzing left and right eyes separately and then combining the results [36], while others use both eyes within a single image [14].…”
Section: B Periocular Face Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that in all cases an improvement between 3 and 5 percent was achieved when using both eyes instead of only one. Thus, most of the state-of-the art methods use the bi-ocular information, some of them analyzing left and right eyes separately and then combining the results [36], while others use both eyes within a single image [14].…”
Section: B Periocular Face Recognitionmentioning
confidence: 99%
“…On the other hand, some works propose feature fusion approach which combines handcrafted features (e.g. LBP and HOG) with features extracted using pretrained CNN models [18], [36]. Another hybrid model is introduced in [1] for ocular smartphone authentication (Selfie Biometrics).…”
Section: B Periocular Face Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, periocular recognition applies to the recognition process around the eye. According to [4], a dualstream convolutional neural network model can be applied to the periocular region to obtain more color information, which means that the network can accept RGB images. In addition, a new descriptor, the orthogonal combinatoriallocal binary coding model, is proposed.…”
Section: Sclera Vasculature and Periocularmentioning
confidence: 99%
“…The idea of sharing parameters imposes prior knowledge that the inputs to each substream (S R , S G , and S B ) are processed concurrently by the network, which substantially reduces the number of parameters in the MSDN; there is some speedup of the optimization process. In addition, this method warrants different layers in each stream be functionally equivalent after training, which is known to be beneficial to preventing extrapolation biases; that is, the network can adapt better to outof-domain examples than networks without shared parameters 35,36 . In addition, the MSDN utilizes the design concept of DenseNet 37 , in which all layers are densely connected (Fig.…”
Section: Shaped Dps In a Multistream Densenetmentioning
confidence: 99%